Rituximab plus fludarabine and cyclophosphamide or other agents in chronic lymphocytic leukemia. Issue 10 (October 2010) - Robak, Tadeusz; Lech-Maranda, Ewa; Robak, Pawel
Over the last few years, several monoclonal antibodies have been investigated in patients with B-cell lymphoid malignancies. Rituximab is the most important monoclonal antibody of clinical value in these disorders. Rituximab is an IgG1 chimeric antibody containing murine light- and heavy-chain variable region sequences and human constant region sequences. Since approval in 1997, rituximab has become the standard of care in follicular B-cell lymphoma, chronic lymphocytic leukemia (CLL) and aggressive lymphoma when combined with chemotherapy. Higher clinical benefits of rituximab can be seen in patients with CLL when it is added to other chemotherapeutic agents. Several recent reports have suggested that in patients with CLL, rituximab combined with purine nucleoside analogs (PNAs) or PNAs and cyclophosphamide may improve the results with acceptable toxicity, both in previously untreated and refractory/relapsed patients. The randomized, multinational Phase III study (REACH trial) has shown that rituximab combined with fludarabine and cyclophosphamide (R-FC regimen) results in 10 months longer progression-free survival, and higher overall response and complete response rates than fludarabine and cyclophosphamide (FC regimen) in previously treated patients. The German CLL study group initiated a multicenter, multinational Phase III trial, CLL8, to evaluate the efficacy and tolerability of R-FC versus FC for the first-line treatment of patients with advanced CLL. The overall response rate was significantly higher in the R-FC arm (95%) compared with FC (88%). The complete response rate in the R-FC arm was 44% compared with 27% in the FC arm. The recently updated analysis has demonstrated longer overall survival in the R-FC group. Recent clinical observations have revealed that combinations of rituximab with pentostatin and cyclophosphamide, or cladribine and cyclophosphamide are also highly active regimens in previously untreated CLL. In addition, the results of treatment with high-dose methylprednisolone in combination with rituximab in advanced CLL resistant to fludarabine have been reported recently by several groups. However, available therapies are only partially effective in CLL, exposing an obvious need to develop new, more specific and active drugs. Recently, several new anti-CD20 monoclonal antibodies have been developed and are now being evaluated in clinical trials.